Development of a novel magnetite–chitosan composite for the removal of fluoride from drinking water: adsorption modeling and optimization. Issue 89 (27th September 2015) - Mohseni-Bandpi, Anoushiravan; Kakavandi, Babak; Kalantary, Roshanak Rezaei; Azari, Ali; Keramati, Azam
<x xml:space="preserve">Abstract</x> Fe3O4–chitosan can be separated both quickly and easily. The magnetization of adsorbents and use of magnetic separation techniques can be an effective way to resolve problems associated with separation and filtration.